Effects of Omega-3 Fatty Acids on Chinese Patients with Cardiovascular Risk Factors: A Systematic Review and Meta-Analysis. Issue 1 (22nd March 2022) - Mei, Zhu; Song, Haixu; Tian, Xiaoxiang; Liu, Dan
Abstract: Objective: Fish oil (FO) contains omega-3 that inhibits inflammation and blood lipid metabolism, giving it a protective cardiovascular effect. Due to dietary habits, a majority of large-scale clinical trials examining FO and cardiovascular health have been conducted in the Caucasian populations. However, the effects of FO on cardiovascular inflammation indicators and blood lipid metabolism in the Chinese population remain unclear. This study aimed to perform a meta-analysis to elucidate the impact of FO on cardiovascular health in the Chinese population. Methods: Web searches were utilized to locate records of clinical trials related to cardiovascular health and consumption of FO capsules or fish containing omega-3 in several databases, including PubMed, Medline, Embase, Cochrane Library, CNKI, and ClinicalTrial.gov, etc. We obtained lipid metabolism and related proinflammatory markers as the study outcome. We used Review Manager 5.4 and Stata 16 for the statistical analysis. If the I 2 ≥ 30%, a random effects model was used, and if the I 2 < 30%, a fixed effects model was used. Results: Twenty eligible trials were shortlisted from >1000 records. The meta-analysis revealed that supplementation with eicosapentaenoic acid and docosahexaenoic acid reduced systolic blood pressure by 1.88  mmHg (95% CI: −4.97 to −1.20, P  = 0.23), diastolic blood pressure by 0.86  mmHg (95% CI: −1.79 to 0.06, P  = 0.07), fasting blood glucose by 0.05 mmol/L (95% CI: −0.16 to 0.06, P  = 0.40), and low-density lipoprotein-cholesterol by 0.12  mmol/L (95% CI: −0.23 to −0.01, P  = 0.04), when compared to placebo. However, these supplements increased high-density lipoprotein-cholesterol by 0.03  mmol/L (95% CI: 0.01 to 0.05, P  < 0.001), when compared to placebo. Dose subgroup analyses examining total cholesterol found that the low-dose group (mean difference = −0.44, 95% CI: −0.55 to −0.34, P < 0.001) demonstrated the best results. Further, results from dose subgroup analyses showed that the all-dose group demonstrated a decrease in tumor necrosis factor (TNF-α) levels among the study subjects, when compared to other groups. Conclusions: Consumption of FO containing omega-3 fatty acids in the Chinese population can improve lipid metabolism and reduce levels of proinflammatory markers. Therefore, it is necessary to vigorously promote the benefits of consuming FO to prevent cardiovascular diseases throughout China.